Rowing Against the Tide: Getting Landowners to Manage Habitat for Their Favorite Wildlife Species, Bobwhites - Thomas V. Dailey; Ronald A. Reitz; Heather J. Scroggins; William T. White; Thomas B. Treiman; Nigel Hoilet (National Quail Symposium Proceedings, 2017)
A primary cause of the decline of northern bobwhite (Colinus virginianus) is that landowners often lack adequate motivation for the arduous task of creating and managing habitat. We gained insight into some of these motivations through survey questionnaires and focus groups in Missouri, and report findings from 3 studies containing 3,057 survey responses during 2004–2007. One of the surveys targeted Conservation Reserve Program (CRP) lands (‘CRP survey’), another lands with potential for bobwhite restoration (‘bobwhite survey’), and the third focused on grassland bird restoration. Landowners in each survey identified bobwhites as the most popular (.80% of respondents chose ‘somewhat’ or ‘very’ ‘important’ to have bobwhites ‘on my land’) natural resource among a list that included deer, turkeys, prairie-chickens, native plants, grassland birds, rabbits, hawks/owls, etc. Bobwhites were highly valued by landowners, but other answers in these surveys revealed many obstacles to habitat management including economics, time, knowledge, skill, and equipment. For example, only 39% of respondents in the bobwhite survey were interested in joining a habitat restoration cooperative, and ,50% of respondents in all surveys were willing to adopt quail-friendly habitat management (prescribed fire, disking, herbicides, moderate grazing, native vegetation, presence of weeds, etc.). Bobwhite restoration programs, because of the gap between landowners’ fondness for quail, but being less willing to take action, must include a comprehensive approach, ranging from local community involvement by agency biologists and non-government organizations to resource-use policy in Washington, D.C.
Keywords: Colinus virginianus; Conservation Reserve Program; habitat management; landowners; northern bobwhite